OPTIMASI DIAMETER LAS TITIK MENGGUNAKAN METODE TAGUCHI PADA PROSES RESISTANCE SPOT WELDING ROBOTIK DI MESIN OTC DAIHEN - Roni, Komar; Imaduddien Ariefa; Rieky Handoko; Anton Harseno; Muhammad Nanang Adi Saputra; Sahal Ahmad Albab (Journal of Mechanical Engineering and Applied Technology, 2025)
Robotic welding technology has become a key component in modern manufacturing, particularly in automotive industries, due to its ability to deliver consistent weld quality and improve efficiency. However, weld quality remains highly dependent on process parameters such as current (Ampere), voltage, electrode movement speed, and heat input. In the context of resistance spot welding (RSW), optimizing these parameters is essential to achieve ideal weld diameters and ensure joint integrity. Previous research has primarily focused on tensile strength, overlooking diameter as a crucial quality metric in precision manufacturing. This study addresses that gap by investigating the influence of four welding parameters—current, voltage, speed, and heat input—on weld diameter using the Taguchi method. An experimental design with L8 orthogonal array was implemented to reduce the number of trials while maintaining robust analysis. The quality characteristic "Smaller is Better" was used to align with industrial diameter standards of 15–16 mm. Signal-to-noise (SN) ratios and ANOVA were applied to identify the most influential factors. The optimal parameter combination was found to be current at 180 A, voltage at 18 V, speed at 80 cm/min, and heat input at 0.2 KJ/mm. Confirmation experiments yielded an average weld diameter of 15.8125 mm, validating the Taguchi prediction and demonstrating the method’s effectiveness in minimizing diameter variation. These findings confirm that all four parameters significantly affect weld diameter and that Taguchi-based optimization can effectively enhance weld quality and manufacturing efficiency